Psychological Effects of Tax Amnesty: An Analysis of Taxpayers' Perceptions of Tax Amnesty Policy in Indonesia - Wibowo, Danny (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research aims to analyse the psychological impact of Indonesia's tax amnesty policy on taxpayer perceptions and compliance behaviour. The research focuses on the industrial and property sectors, which play a strategic role in asset reporting and legalisation. Using a qualitative case study approach, data were collected through in-depth interviews with selected informants using purposive sampling. The findings show that participation in the tax amnesty program was primarily driven by fear of audits, investigations, and sanctions, rather than by a genuine awareness of tax obligations. The property sector showed more substantial support, viewing the program as a means of legitimising assets and securing financial backing for large-scale projects. In contrast, compliant taxpayers expressed feelings of injustice, believing the policy disproportionately favoured those who had previously evaded taxes. Although overall perceptions of the tax amnesty are positive—particularly among previously non-compliant groups—its long-term effectiveness is uncertain without consistent law enforcement and visible fiscal fairness. This study emphasises the significance of addressing psychological aspects and fairness perceptions in the implementation of fiscal policy to develop a credible and sustainable tax system.